Organotellurium(II) and -(IV) compounds with Picolinoylbis(thioureas): from simple 1 : 1 adducts to multimetallic aggregates - Santos, Sailer Santos dos; Schwade, Vania D.; Lang, Ernesto Schulz; Pham, Chien Thang; Roca Jungfer, Maximilian; Abram, Ulrich; Nguyen, Hung Huy (European journal of inorganic chemistry, 2024)
Reactions of 2,6-dipicolinoylbis(N,N-diethylthiourea) (H2LEt) with common tellurium(IV) starting materials such as PhTeBr3 or TeBr4 yield various tellurium(IV) and tellurium(II) compounds depending on the conditions applied. Equimolar amounts of H2LEt and PhTeBr3 give the 1 : 1 complex [PhTeIVBr3(H2LEt)], while with an excess of H2LEt, the tellurium compound is partially reduced and a PhTeII+ building block coordinates to both sulfur atoms of H2LEt under the formation of the ion pair [PhTeII(H2LEt)][PhTeIVBr4]. Similar reactions between H2LEt and TeBr4 give the neutral monomer [TeIIBr2(H2LEt)] or the coordination polymer [TeIIBr2(H2LEt)]∞. The latter compound is also formed with the assistance of Pb2+ ions. While the lead ions do not appear in the isolated product, similar reactions with transition metal ions such as Ni2+, Mn2+, or Co2+ result in the formation of heterobimetallic complexes, in which Te(II) building blocks are directed to the sulfur atoms of the deprotonated ligand H2LEt2-S,S2−, while the transition metal ions occupy central coordination positions between two of the organic ligands using the pyridine nitrogen atom, carbonyl oxygen atom(s) and/or the nitrogen atoms of the thiourea units.